Functionalized Bacterial Cellulose Microparticles for Drug Delivery in Biomedical Applications - Ullah, Hanif; Badshah, Munair; Correia, Alexandra; Wahid, Fazli; Santos, Hélder A.; Khan, Taous (Current Pharmaceutical Design, 2019)
Background: Bacterial cellulose (BC) has recently attained greater interest in various research fields, including drug delivery for biomedical applications. BC has been studied in the field of drug delivery, such as tablet coating, controlled release systems and prodrug design. Objective: In the current work, we tested the feasibility of BC as a drug carrier in microparticulate form for potential pharmaceutical and biomedical applications. Methods: For this purpose, drug-loaded BC microparticles were prepared by simple grinding and injection moulding method through regeneration. Model drugs, i.e., cloxacillin (CLX) and cefuroxime (CEF) sodium salts were loaded in these microparticles to assess their drug loading and release properties. The prepared microparticles were evaluated in terms of particle shapes, drug loading efficiency, physical state of the loaded drug, drug release behaviour and antibacterial properties. Results: The BC microparticles were converted to partially amorphous state after regeneration. Moreover, the loaded drug was transformed into the amorphous state. The results of scanning electron microscopy (SEM) showed that microparticles had almost spherical shape with a size of ca. 350-400 μm. The microparticles treated with higher drug concentration (3%) exhibited higher drug loading. Keeping drug concertation constant, i.e., 1%, the regenerated BC (RBC) microparticles showed higher drug loading (i.e., 37.57±0.22% for CEF and 33.36±3.03% for CLX) as compared to as-synthesized BC (ABC) microparticles (i.e., 9.46±1.30% for CEF and 9.84±1.26% for CLX). All formulations showed immediate drug release, wherein more than 85% drug was released in the initial 30 min. Moreover, such microparticles exhibited good antibacterial activity with larger zones of inhibition for drug loaded RBC microparticles as compared to corresponding ABC microparticles. Conclusion: Drug loaded BC microparticles with immediate release behaviour and antibacterial activity were fabricated. Such functionalized microparticles may find potential biomedical and pharmaceutical applications.
Keywords: microparticles